Using personal digital assistants to access drug information. - McCreadie SR; Stevenson JG; Sweet BV; Kramer M (American Journal of Health-System Pharmacy, 2002)
The use of personal digital assistants (PDAs) to access drug information in a health system is described. Given the widespread use of PDAs at an 872-bed university health system, an opportunity existed to provide current drug information to physicians via these devices. As part of the health system's intranet, extensive online content had been made available through a browser; extension to PDAs was a natural next step. There were two primary requirements: the ability to synchronize information with the database server when a PDA was used and the development of content and applications by using existing staff. Mobile enterprise software was chosen that supports multiple PDA platforms, is easy to use, and does not require programming skills. The software works through customized 'channels,' or collections of information from a content provider. The customized channel service works over the Internet. Two channels of content were created, an ambulatory care channel and an inpatient care channel. The ambulatory care channel contains a list of preferred ambulatory care agents, poison control information, the locations of outpatient pharmacies, drug information, and safety tips for prescribing. The inpatient channel contains the inpatient formulary, current news and events, information on currrent drug shortages and recalls, pharmacy contact information, and medication safety tips. When a user synchronizes his or her PDA, the software contacts the department's intranet servers and processes the request. The data are compressed and downloaded to the user's PDA. A university health system successfully used PDAs to access drug and other information.